Bone Morphogenetic Protein in Scaphoid Nonunion: A Systematic Review - Polmear, Michael M.; Anderson, Ashley B.; Lanier, Paul J.; Orr, Justin D.; Nesti, Leon J.; Dunn, John C. (Journal of Wrist Surgery, 2021)
Background Scaphoid nonunion can lead to carpal collapse and osteoarthritis, a painfully debilitating problem. Bone morphogenetic protein (BMP) has been successfully implemented to augment bone healing in other circumstances, but its use in scaphoid nonunion has yielded conflicting results.Case Description The purpose of this study is to assess the outcomes and complications of scaphoid nonunion treated surgically with BMP.Literature Review A literature review of all available journal articles citing the use of BMP in scaphoid nonunion surgery from 2002 to 2019 was conducted. We included studies that used BMP as an adjunct to surgical treatment for scaphoid nonunions in both the primary and revision settings with computed tomography determination of union. Demographic information, dose of BMP, tobacco use, outcomes, and complications were recorded. A total of 21 cases were included from four different studies meeting inclusion criteria.Clinical Relevance The union rates were 90.5% overall, 100% for primary surgeries, and 77.8% for revision surgeries. Five patients (24%) experienced 11 complications, including four cases (19%) of heterotrophic ossification. Use of BMP in scaphoid nonunion surgery resulted in a 90.5% overall union rate but was also associated with complications such as heterotopic ossification. All included studies used BMP to augment bone graft, screw or wire fixation, or a combination of methods. The efficacy of BMP in scaphoid nonunion is unclear, and a sufficiently powered, randomized controlled trial is needed to determine optimal fixation methods, dosing, and morbidity of the use of BMP.Level of Evidence This is a Level IC, therapeutic interventional study.
Keywords: scaphoid; scaphoid fracture; bone morphogenetic protein; scaphoid fixation; scaphoid nonunion